PENGUATAN PEMAHAMAN KEAGAMAAN DAN LITERASI KEUANGAN REMAJA DI KAWASAN EKS LOKALISASI BANDAR BARU - Bagus Ramadi; Sri Wulandari; Syahla Nabila; Besty Aprilia; Alifia Haira Harahap (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The former Bandar Baru red-light district is a region that faces social challenges, especially for teenagers growing up in a dynamic and diverse community. Low levels of religious understanding and financial literacy are among the factors influencing their behavior and lifestyle. This community service program aims to strengthen religious understanding and financial literacy among teenagers through a collaborative educational outreach model between Gatra Adiwangsa Community Service Program (KKN) students from the State Islamic University of North Sumatra and the BOPTN-PkM program from the State Islamic University of North Sumatra. The activities were carried out through several sessions, including the Love, Pride, Understand the Rupiah (CBPR) socialization program, the Care, Recognize, Complain (PEKA) program, an introduction to the QRIS digital payment system, and religious outreach themed